(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Protecting and strengthening children’s health is one of the priority directions of any society. Compliance with sanitary and hygiene requirements in children’s institutions — preschool educational organizations, schools, boarding schools, and specialized childcare institutions — particularly the provision of clean drinking water, plays a decisive role in ensuring healthy growth and development, preventing infectious diseases, and creating a safe educational environment. According to the World Health Organization (WHO), children’s bodies are highly sensitive to contaminated water, and intestinal infections, parasitic diseases, and illnesses transmitted through poor sanitation are widely spread among children [7, 8]. This article highlights the importance of providing clean drinking water in children’s institutions, its impact on health, existing requirements and recommendations, as well as key aspects of the issue based on national and international experience.